PROBLEMA RELASI KUASA ANTARA LEMBAGA ADAT DENGAN PEMERINTAH DESA (Studi Eksplanatif Tentang Relasi Pemerintah dan Lembaga Adat di Desa Pa’ Pala Kecamatan Krayan Timur Kabupaten Nunukan Provinsi Kalimantan Utara) - Lerry Chandra; Jaka Triwidaryanta (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
The problem of power relations between traditional institutions as a community unit (self-governing community) and the Village Government has not had a substantial impact on the welfare of the residents. The power relations between traditional institutions and the village government failed to realize the character of local institutions in realizing deliberative democracy based on local values ​​in the practice of using culture-based structures and power to maintain village dignity. This study uses a qualitative explanatory method to explain the workings of democracy through customary government systems and efforts to create prosperity. Primary data was taken through interviews, observation, and discussion. Secondary data was collected through village documents, journals, and books. The explanatory analysis combines dialogue between village government document facts, with local voices to realize knowledge findings. The results of the study indicate that the customary institutions in Pa' Pala Village, which are located as social organizations or deliberations and agreements as well as legal holders, are formal in nature, the space for accommodating community aspirations is not yet optimal for the welfare of the residents